2016
DOI: 10.1080/01612840.2016.1198946
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Screening, Brief Intervention, and Referral to Treatment (SBIRT) Education for Registered Nurses and Behavioral Health Professionals

Abstract: Although substance use is prevalent in the United States, the majority of people who misuse substances do not receive appropriate treatment. This paper describes, (1) an interprofessional education (IPE) program for health professionals to provide Screening Brief Intervention and Referral to Treatment to rural substance use patients, and (2) compares registered nurses' [RNs] and behavioral health professionals' [BHPs] attitudes to work with those patients and their perceptions on IPE. A data analysis of 62 RNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…All studies were reviewed for age, race and gender, with the majority of the studies (n = 5) reporting no demographic data. Age and gender were reported by four studies (Corrigan, Palmer, & Olson, 2018;Puskar et al, 2016;Tran, Stone, Fernandez, Griffiths, & Johnson, 2009a;Tran et al, 2009b) with the mean age ranging from 31.4-42.7 and gender being predominantly female (89%-92%). Race was addressed in only two studies (Corrigan et al, 2018;Puskar et al, 2016) with little diversity noted, white/Caucasian (86.1% and 96.7% respectively), black (8.3% and 3.3% respectively) and "other" reported as 5.6% (Puskar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were reviewed for age, race and gender, with the majority of the studies (n = 5) reporting no demographic data. Age and gender were reported by four studies (Corrigan, Palmer, & Olson, 2018;Puskar et al, 2016;Tran, Stone, Fernandez, Griffiths, & Johnson, 2009a;Tran et al, 2009b) with the mean age ranging from 31.4-42.7 and gender being predominantly female (89%-92%). Race was addressed in only two studies (Corrigan et al, 2018;Puskar et al, 2016) with little diversity noted, white/Caucasian (86.1% and 96.7% respectively), black (8.3% and 3.3% respectively) and "other" reported as 5.6% (Puskar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies used the same instrument (Corrigan et al, 2018;Rosenthal et al, 2018) therefore comparing outcomes between interventions was limited. Opioid use disorder educational needs of medical-surgical nurses were identified by institutional survey results (Naqib et al, 2018), self-reported knowledge gaps (Rosenthal et al, 2018;Tran et al, 2009b), and an institution identified need secondary to an increased population of patients with OUD in medical-surgical areas (Corrigan et al, 2018;Graham, Christy, Emmitt-Myers, & Zyzanski, 1997;Puskar et al, 2016;Russell et al, 2017;Sargsyan, Metcalfe, Turner, & Fouts, 2013;Tran et al, 2009b). Once identified, educational programmes were developed to increase competency in the areas of need.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these findings suggest there are considerable gaps across the curriculum, government sponsored training programs, such as those promoting use of the SBIRT model (Screening, Brief Intervention and Referral to Treatment), may offer opportunities to build foundation and advanced content on concise substance abuse treatment and prevention education that focuses on the intersections of addiction, minority status, and related factors. Such training programs have been found to be successful across the U.S. (Gotham et al, 2015;Puskar et al, 2016) providing interprofessional experiences across disciplines, diverse settings, as well as providing strong evidence for the linkage between education and social work practice (Russett, 2015). For more information on the SBIRT model, please see http://www.integration.samhsa.gov/clinical-practice/sbirt Role of faculty.…”
Section: Discussionmentioning
confidence: 99%